ANTARA ELING DAN RAGU: ANALISIS PSIKOLOGI SASTRA NOVEL DEWI KAWI - Astadi, I Gede Iwan (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 Analysis of the psychology literature of Dewi Kawi want to describe the structural aspects and psychological aspects of character. Theory used in this study are structural theory and the theory of personality psychology. Methods and techniques used in this study were divided into three stages. Methods and techniques used in this study were divided into three stages. Methods and techniques of providing data, methods and techniques of data analysis, data presentation methods and techniques. At the stage of providing data using method of listening that assisted with recording techniques and translation techniques. Stage of data analysis using qualitative and descriptive analytic techniques. Stage presentation of data using informal methods of deductive and inductive techniques. Results achieved in this study the structure of Dewi Kawi that includes theme, plot, character and characterization and setting,. Moreover, the psychological aspects of characters Dewi Kawi that includes the id, ego, and superego. Psychology conflict between the characters in Dewi Kawi that include Psychology conflict Eling vs ragu, Psychology conflict Eling vs Kawi and Psychology conflict Podo vs Eling. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: short story, structure, psychology